Molecular pathogenesis of long QT syndrome type 2. Issue 5 (22nd January 2016) - Smith, Jennifer L.; Anderson, Corey L.; Burgess, Don E.; Elayi, Claude S.; January, Craig T.; Delisle, Brian P.
Abstract: The molecular mechanisms underlying congenital long QT syndrome (LQTS) are now beginning to be understood. New insights into the etiology and therapeutic strategies are emerging from heterologous expression studies of LQTS‐linked mutant proteins, as well as inducible pluripotent stem cell derived cardiomyocytes (iPSC‐CMs) from LQTS patients. This review focuses on the major molecular mechanism that underlies LQTS type 2 (LQT2). LQT2 is caused by loss of function (LOF) mutations in KCNH2 (also known as the human Ether‐à‐go‐go‐Related Gene or hERG ). Most LQT2‐linked mutations are missense mutations and functional studies suggest that ~90% of them disrupt the intracellular transport (trafficking) of KCNH2 ‐encoded Kv11.1 proteins to the cell membrane. Trafficking deficient LQT2 mutations disrupt Kv11.1 protein folding and misfolded Kv11.1 proteins are retained in the endoplasmic reticulum (ER) until they are degraded in the ER associated degradation pathway (ERAD). This review focuses on the quality control mechanisms in the ER that contribute to the folding and ERAD of Kv11.1 proteins; the mechanism for ER export of Kv11.1 proteins in the secretory pathway; different subclasses of trafficking deficient LQT2 mutations; and strategies being developed to mitigate or correct trafficking deficient LQT2‐related phenotypes.